Possible impact of antioxidant intake on composite dietary antioxidant index and the progression of benign prostatic hyperplasia: an observational study - Xuanyu Hao; Dongyang Li (BMC Public Health)
Abstract Objective We aim to evaluate the association of composite dietary antioxidant index (CDAI) and Benign Prostatic Hyperplasia (BPH) in a large population in the United States using a cross-sectional design. Methods Data was retrieved from the National Health and Nutrition Examination Survey (NHANES) 2003–2008 and 2013–2020 datasets. Univariate and multivariate logistic regression were performed to explore the association between CDAI and BPH. The restricted cubic spline (RCS) model was also conducted to investigate the potential linear relationship. Sub-group analyses were also conducted. Results Totally, this study included 13,419 participants with 1085 BPH patients among them. The higher continuous CDAI value was significantly related to higher BPH risk (OR = 1.05, 95%CI: 1.02, 1.08). Besides, individuals with the highest quartile (Q4) CDAI possessed 1.87 times risk of BPH than the lowest quartile (Q1, OR = 1.87, 95%CI: 1.41, 2.50). The RCS curve also showed a positive linear dose-response relationship between CDAI and BPH (cut-off = -0.64). The P for interaction in any subgroup was > 0.05, indicating that the main outcome was not affected by other covariates. The limitation of this study was the lack of data on the relationship between CDAI and the severity of BPH symptoms. Conclusions This study reveals that an elevated CDAI may be associated with a linear higher risk of BPH. We do not recommend intentional or excessive antioxidant diet to prevent BPH based on the current results.